Synthesis and selectivity of 1-methoxycarbonylmethyl-3-arylamino-7-bromo-5-phenyl-1,2-dihydro-3H-1,4-benzodi- azepin-2-ones binding for CNS benzodiazepine receptors - Burenkova, N.A.; Pavlovsky, V.I.; Oleinich, I.A.; Boyko, I.A.; Makan, S.Yu.; Artemenko, A.G.; Kuz’min, V.E. (Інститут молекулярної біології і генетики НАН України, 2009)
Earlier, the methoxycarbonylmethyl fragment at the 1-position and the nitrophenylamine fragment at the 3-position of the 1,4-benzodiazepine ring, on the base of the QSAR analysis of series of 1,4-benzodiazepin-2-one derivatives [1], have been shown to gave compounds with increased affinity for peripheral benzodiazepine receptors (PBR). The 3-arylamine derivatives of 1-methoxycarbonylmethyl-7-bromo-5-phenyl-1,2-dihydro-3H-1,4-benzodiazepin-2-one were proposed for the directed synthesis as a promising high selective ligands of PBR. The target compounds were synthesized through the condensation of 1-methoxycarbonylmethyl-3-chloro-7-bromo-5-phenyl-1,2-dihydro-3H-1,4-benzodiazepin-2-one with substituted anilines. Affinities of synthesized compounds for the CNS benzodiazepine receptors of peripheral (PBR) and central (CBR) types were determined by the radioligand method in vitro. Selective PBR ligand with a high affinity — 1-methoxycarbonylmethyl-3-(2'-nitro)phenylamino-7-bromo-5-phenyl-1,2-dihydro-3H-1,4-benzodiazepin-2-one, 7 (MX-1785, Ki(PBR)=19.1 nM, Ki(CBR)>10000 nM) was found among the studied compounds. Раніше на підставі результатів QSAR-аналізу ряду похідних 1,4-бенздіазепін-2-ону [1] було показано, що наявність метоксикарбонілметильного фрагменту в положенні 1 і нітрофеніламінного фрагменту в положенні 3 1,4-бенздіазепінового циклу сприяють прояву високого афінітету до периферичних бенздіазепінових рецепторів (ПБДР). Для цілеспрямованого синтезу були запропоновані 3-ариламінопохідні 1-метоксикарбонілметил-7-бром-5-феніл-1,2-дигідро-3Н-1,4-бенздіазепін-2-ону як перспективні високоафінні ліганди ПБДР. Конденсацією 1-метоксикарбонілметил-7-бром-3-хлор-5-феніл-1,2-дигідро-3Н-1,4-бенздіазепін-2-ону із заміщеними анілінами синтезовано цільові сполуки. Методом радіолігандного аналізу в експериментах in vitro вивчено афінітет синтезованих сполук до бенздіазепінових рецепторів ЦНС периферичного (ПБДР) і центрального (ЦБДР) типів. У ряді досліджених сполук виявлено високоафінний і селективний ліганд ПБДР — 1-метоксикарбонілметил-3-(2'-нітро)феніламіно-7-бром-5-феніл-1,2-дигідро-3Н-1,4-бенздіазепін-2-он, 7 (МХ-1785, Ki(ПБДР)=19,1 нМ, Ki(ЦБДР)>10000 нМ)